2017
DOI: 10.1080/17436753.2017.1356043
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of β-TCP/bioglass/zirconia scaffolds

Abstract: Tricalcium phosphate scaffolds reinforced with bioglass were characterised morphologically, physically, and mechanically. The scaffolds were fabricated through powder technology and the polymer foaming technique using 80 wt-% of β-TCP and 20 wt-% of phosphate-based bioglass doped with zirconia in various amounts (0, 0.25, 0.5, 0.75, and 1.0 wt-%). The foaming agent was varied (1, 1.5, 2, 2.5, and 3 wt-%) to determine the optimal amount that ensured an interconnected porosity and pore size suitable for increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Pyrolysis consists of decomposing the polymeric binder at a temperature of 500°C and sintering provides mechanical resistance to the scaffold by forming necks between particles. In a previous investigation by C. Ruiz-Aguilar et al [ 20 ], the addition of the binder and foaming agent was analyzed in various chemical compositions of the scaffolds; the scaffolds were cooled inside the muffle furnace, with a cooling time of 10°C/min, until they reached room temperature and the samples were removed. They concluded that the best results of the chemical, structural, and physical characterization for applications in long bones (tibia, femur, and fibula) were those obtained by the V1, VZ0.5, and VZ1 samples.…”
Section: Methodsmentioning
confidence: 99%
“…Pyrolysis consists of decomposing the polymeric binder at a temperature of 500°C and sintering provides mechanical resistance to the scaffold by forming necks between particles. In a previous investigation by C. Ruiz-Aguilar et al [ 20 ], the addition of the binder and foaming agent was analyzed in various chemical compositions of the scaffolds; the scaffolds were cooled inside the muffle furnace, with a cooling time of 10°C/min, until they reached room temperature and the samples were removed. They concluded that the best results of the chemical, structural, and physical characterization for applications in long bones (tibia, femur, and fibula) were those obtained by the V1, VZ0.5, and VZ1 samples.…”
Section: Methodsmentioning
confidence: 99%
“…This combo stent showed excellent endothelial progenitor cell adhesion capability from the circulating system with the antibody coatings ( Figure 9 ). In bone repair engineering, composites like collagen/HA, β-TCP/collagen, HA/Starch, HA/gelatin, and PCL/HA are frequently reported for surface modification ( Butscher et al, 2013 ; Ruiz-Aguilar et al, 2017 ; Ho-Shui-Ling et al, 2018 ; Prabakaran et al, 2021 ). It was described that hydrogel coatings loaded with active enzymes coated on top of a titanium plate could significantly stimulate osteoblast colonization and growth ( Muderrisoglu et al, 2018 ).…”
Section: Inorganic Surfaces Functionalized By Organic Moleculesmentioning
confidence: 99%
“…Zirconium as zirconium oxide has been used in the biomedical field for dental [ 175 ] and bone implants due to its superior mechanical properties and cytocompatibility [ 176 – 195 ]. Enhancement in mechanical stability and hydroxyapatite formation in silicate, borate, and phosphate bioactive glasses has been observed by incorporating zirconium [ 183 , 196 198 ]. Yadav et al [ 197 ] reported that the addition of zirconium (up to 2.0 wt.%) in 13–93 bioactive glass resulted in a significantly faster dissolution rate and a higher pH of SBF solution dependent on the zirconium concentration.…”
Section: Bioactive Glasses Doped With Other Elementsmentioning
confidence: 99%